Multiparametric structural imaging biomarkers of early white matter microstructural changes during and after glioblastoma chemoradiotherapy: diffusion tensor imaging and diffusion kurtosis imaging - Lučić, Miloš A.; Djan, Igor; Šveljo, Olivera; Lučić, Silvija; Ivanov, Olivera; Bjelan, Mladen; Ilić, Dušan (Vojnosanitetski pregled, 2026)
Background/Aim. Recognizing early irradiation-induced changes in the white matter is of great importance. The aim of this study was to investigate the potential use of diffusion tensor imaging (DTI) and diffusion kurtosis imaging (DKI) parameters as biomarkers of early brain tissue microstructural changes during chemoradiotherapy (CRT) treatment of newly diagnosed glioblastoma. Methods. A total of 42 glioblastoma patients who underwent CRT after surgical resection/biopsy were scanned three times using magnetic resonance imaging (MRI): before treatment, after 16 fractions, and after 33 fractions. Regions of interest (ROI) with total irradiation doses of 59.4 Gy (ROI 1), 39.6 Gy (ROI 2), and 19.8 Gy (ROI 3) were identified using co-registered axial dose distribution plans/dose-volume histograms and MRI scans. For each ROI, the following DTI parameters were calculated, measured, and analyzed: fractional anisotropy (FA), radial diffusivity (RD), axial diffusivity (AD), and mean diffusivity (MD). The corresponding DKI parameters included: radial kurtosis (RK), axial kurtosis (AK), and mean kurtosis (MK). Results. A significant decrease in FA value was observed in ROI 1 (total delivered dose 59.4 Gy) after both 16 and 33 delivered fractions, while the other DTI parameters and MK showed a significant increase. In ROI 1, a decreasing trend in RK and AK was identified, which was statistically confirmed after both 16 and 33 delivered fractions. In ROI 2 (total delivered dose of 39.6 Gy), FA values were significantly reduced after both 16 and 33 fractions, whereas RD, AD, MD, and MK were increased after 16 fractions, followed by a decrease after 33 fractions. The RK value in ROI 2 showed a significant decrease after both 16 and 33 fractions, and no changes were observed in AK values. In ROI 3 (total delivered dose of 19.8 Gy), no significant changes in any of the measured DTI or DKI parameters were noticed. Conclusion. DTI and DKI metric parameters may serve as biomarkers of early changes during and after CRT, providing information that may offer a better understanding of the complex dynamics of early white matter microstructural changes in response to glioblastoma CRT.
Keywords: biomarkers; brain injuries; chemoradiotherapy; diffusion magnetic resonance imaging; diffusion tensor imaging; glioblastoma.